DIRECT MEDICAL COSTS AND ASSOCIATED FACTORS AMONG OUTPATIENTS WITH NON-COMMUNICABLE DISEASES AT GO VAP DISTRICT MEDICAL CENTER, 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate direct medical costs (DMCs) and identify disease-specific factors associated with these costs among health insurance-covered outpatients with non-communicable diseases (NCDs) at Go Vap District Medical Center in 2025.Subjects and Methods: A retrospective cross-sectional study of 301 outpatient visits by patients whose principal ICD-10 diagnosis was hypertension, type 2 diabetes mellitus, cardiovascular disease or chronic kidney disease, from January to June 2025. Costs were estimated using a bottom-up approach. Associated factors were examined with log-linear regression using HC3 robust standard errors, fitted separately for the whole sample and for the hypertension and type 2 diabetes subgroups.Results: The mean direct medical cost was 353,032 ± 137,214 VND per visit (median 336,695 VND). Laboratory tests accounted for the largest share of total costs (62.5%), followed by medications (17.9%), consultation (10.1%) and imaging/functional testing (9.5%). Health insurance reimbursed 90.4% and patients paid 9.6% of total direct medical costs. After multivariable adjustment, the number of laboratory tests, the number of imaging/functional tests and the 100% insurance benefit level were consistently associated with costs across all three models (p < 0.001). The number of drug classes was associated with costs only in the diabetes subgroup (p = 0.002); comorbid chronic kidney disease was not significantly associated with costs in any model.Conclusion: Laboratory testing was the largest component of direct medical costs for outpatient NCD care at the primary care level. Because the number of laboratory and imaging tests is itself a component of total cost, the observed associations are partly definitional; studies assessing the appropriateness of test ordering against clinical guidelines are needed before cost-containment interventions are recommended.
Keywords: Direct medical costs; non-communicable diseases; Health insurance; Hypertension; Type 2 diabetes mellitus; Go Vap District.